Optimizing Digging Equipment Productivity Using Overall Equipment Effectiveness (OEE) Method in Coal Overburden Mining Activities - Prabowo, Heri; Hutmi, Rahul; Dewata, Indang (Universitas Negeri Padang, 2023)
Coal companies have an overburden stripping production target of 95,000 bcm in January 2022, while the realization of production with the Sumitomo SH 350 LHD excavator and Hitachi Zaxis 350 H excavator is only 77,000 bcm or 82% of the production target. The purpose of this study was to obtain an analysis of the productivity of the Sumitomo SH 350 LHD Excavator (40) and Hitachi Zaxis 350 H Excavator (31) in the overburden stripping activity in January 2022, analyze the obstacle factors that caused the available working hours to be reduced by using the Fishbone diagram method, get an analysis of the Overall Equipment Effectiveness (OEE) value of the Sumitomo SH 350 LHD Excavator (40) and Hitachi Zaxis 350 H (31) Excavator before being optimized, and get the analysis and productivity of the Sumitomo SH 350 LHD Excavator (40) and the Hitachi Zaxis 350 H Excavator (31) which has been optimized with the implementation of Overall Equipment Effectiveness (OEE) to achieve the overburden stripping production target. After analysis and improvement efforts, the total overburden stripping production was 149,000 bcm, which means that it has reached the target and even exceeded the production target of 95,000 bcm/month with the OEE value of the digging equipment of 41% and 43%, respectively. However, the OEE value is still very low compared to the world-class standard OEE value, which is 85% and there is still room for improvement.